2023
DOI: 10.3390/ani13101581
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing NUtrack to Access the Activity Levels in Pigs with Varying Degrees of Genetic Potential for Growth and Feed Intake

Dalton Obermier,
Melanie Trenahile-Grannemann,
Ty Schmidt
et al.

Abstract: Feed cost accounts for over two-thirds of the variable cost of production. In order to reduce feed costs without sacrificing production numbers, feed efficiency must be improved. Calorie expenditure has been difficult to quantify in the past but is understood to impact residual feed intake (RFI) greatly. The objective of this work was to utilize an advanced computer vision system to evaluate activity levels across sex and sire groups with different expected breeding value combinations for growth and feed intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Intuitively, time spent lying and distance traveled are expected to have the strongest genetic correlations with ADG, as an animal that expends less energy is expected to grow faster. Obermier et al [ 16 ] also found that pigs that spent more time lying and that were less active had higher growth rates and greater body weight at a given age. Sitting time was the behavior trait that was estimated to be least phenotypically and genetically correlated with all production traits, while distance was estimated to be the most correlated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intuitively, time spent lying and distance traveled are expected to have the strongest genetic correlations with ADG, as an animal that expends less energy is expected to grow faster. Obermier et al [ 16 ] also found that pigs that spent more time lying and that were less active had higher growth rates and greater body weight at a given age. Sitting time was the behavior trait that was estimated to be least phenotypically and genetically correlated with all production traits, while distance was estimated to be the most correlated.…”
Section: Resultsmentioning
confidence: 99%
“…Behavior traits that are genetically correlated to production traits can be used for genetic improvement, including activity levels [ 16 ], eating patterns [ 17 ], and management refinement [ 18 ]. The goal of this study was to create a data quality control procedure and investigate behavior traits that can be captured by digital phenotyping and their phenotypic and genetic correlations with production traits.…”
Section: Introductionmentioning
confidence: 99%